The effect of flexible work arrangements on ethical decision-making - Normasari, Pradita Sita Devi; Sjabadhyni, Bertina (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
This study aimed to compare the impact of different types of flexible work arrangements (flextime and telecommuting) on ethical decision-making. Ethical decision-making is when individuals use their moral basis to determine what is right and wrong in a given situation. It involves an awareness of moral dilemmas and consideration of the consequences of decisions. Flexible work arrangements are offered to promote individuals’ ethical decision-making by balancing their needs at work and outside work, such as spending time with family. This research was conducted on 185 employees and used a quantitative approach that utilizes experimental methods with a post-test-only design. Employees’ ethical decision-making was measured using two vignettes. Data analysis was conducted using the independent sample t-test parametric statistical technique. The study results indicated a t = 4.21 and a significance level of .00 (p < .05), which showed that this study's working hypothesis was acceptable. It concluded that there were differences in ethical decision-making between two types of flexible work arrangements: flextime and telecommuting groups.